Study guides

☆☆

Q: How do you solve a squared plus a plus ab plus b equals 0?

Write your answer...

Submit

Still have questions?

Related questions

A = 1, B = 9

to solve ab=c+a for a:Divide both sides by b, so:a= (c+a)/b

2ab

yes because ab plus bc is ac

(a + x^2)(b + y^2)

The square root of 149 (7 squared plus 10 squared equals 149).

b2 + ab - 2 - 2b2 + 2ab = -b2 + ab - 2 which cannot be simplified further.

Commutativity.

7

No. A times B = AB

(a+b)(a squared-ab+b squared)

The existence of the additive inverse (of ab).

3y=ab. Divide by 3 to get y=ab/3

associative property

x2y + axy + abx + a2b Factor by grouping. xy(x + a) + ab(x + a) (xy + ab)(x + a)

the midpoint of AB.

C minus B equals AB

8 1/3 = ab^-1, 1.8 =ab^2

The problem here is nobody knows if "ay squared" is (ay)2 or ay2 etc. To solve a mathematical problem it must be set out mathematically or nobody knows your intention. Here is a sort of mathematical statement which is unclear, and although it ends in a question mark, nobody knows what the question is, even if you do. Try again and people will do their best to answer it. I read the question as: x2y2 + ay2 + ab + bx2 ? But what is required to be done with it?

ab=1a+1b a is equal to either 0 or two, and b is equal to a

If, as is normal, ab represents a times b, etc then ab + ab + cc = 2ab + c2 which is generally not the same as abc.

No, A+B is left as A+B AB would be A x B

An exothermic chemical reaction.

NM equals 2x + 1, as stated in the question!

This expression can be factored. ab + 3a + b2 + 3b = a(b + 3) + b(b + 3) = (a + b)(b + 3)